A1-L1(2) structures in the Al-Co-Ni-Ti quaternary phase system - Minshull, James P.; Neumeier, Steffen; Tucker, Matthew G.; Stone, Howard J. (2011)
The phase constituents of alloys from the (Ni,Co)(85)(Al,Ti)(15) plane of the Ni-Co-Al-Ti quaternary system were investigated following prolonged exposure at 750 degrees C. Microstructural investigations confirmed the existence of a continuous A1-L1(2)) two-phase region in the Ni-Co-Al-Ti quaternary system between Ni-Ni3Al and Co-Co3Ti. The lattice misfits of alloys from this quaternary system were determined using neutron diffraction. With increasing contents of Ti the positive lattice misfit increases up to +0.79% in the Ti-containing alloys, which leads to an increasing tetragonal distortion of the gamma matrix phase due to the increasing coherency stresses.
Keywords: Lattice misfit; neutron diffraction; Phase diagrams; Ni-Co-superalloys